PROFIL PROGRAM CONTINUOUS PROFESSIONAL DEVELOPMENT (CPD) GURU BIOLOGI DI WILAYAH JAWA BARAT DALAM UPAYA MENINGKATKAN KUALITAS PROFESI (Profile of Continuous Professional Development Program of Biology Teachers in West Java in an Effort to Enhance Their Ow - Rahmat, Adi; M.Si., Amprasto; Riandi, Dr.; Saefudin, Dr.; Sutarno, Nono (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2011)
A study on the profile of the continuous professional development (CPD) program of biology teacher in West Java has been done descriptively since March until November 2010. The study was aimed to obtain several information about professional activities have been being followed by biology teachers in West Java. This information was then used to draw CPD profile conducted by biology teachers in an effort to enhance their competencies and their professional quality. Respondents of the study were biology teachers qualified to follow teacher certification and employing in senior high schools of 11 cities in West Java. Information about perceptions of the teacher on teacher improvement programs, the forms of the professional activities of the teacher and the sources supporting the teacher to follow those activities were collected using questionaire. The result shown that biology teachers in West Java had good perception on improving the quality of the teacher and there are eight forms of professional activity which were followed by biology teachers in West Java in an effort to enhance their own professional quality. The seven forms of professional activities were Education and Training (Diklat), Workshop, Seminar, writing teaching material, visiting scientific institutions, doing research, writing and publishing article and/or a textbook. Three out of those seven forms of professional activity had high teacher involvement scale, which indicated that they were preferred by biology teacher. The three forms professional activities were Education and Training, Seminar, and Workshop. However, the number of each professional activity followed by teacher in the last three years was very low (less than one activity each year) due to several reasons. The four main reasons were no permission from school principal interconnecting with teacher task in the school, distance to the place of professional activities, financial, and teacher family.Key words: biology teacher, teacher quality, professional activity of the teacher, continuous professional development (CPD) program